Altered intracellular localization and mobility of SBDS protein upon mutation in Shwachman-Diamond syndrome. - Claudia Orelio (Public Library of Science (PLoS), 2011)
Shwachman-Diamond Syndrome (SDS) is a rare inherited disease caused by mutations in the SBDS gene. Hematopoietic defects, exocrine pancreas dysfunction and short stature are the most prominent clinical features. To gain understanding of the molecular properties of the ubiquitously expressed SBDS protein, we examined its intracellular localization and mobility by live cell imaging techniques. We observed that SBDS full-length protein was localized in both the nucleus and cytoplasm, whereas patient-related truncated SBDS protein isoforms localize predominantly to the nucleus. Also the nucleo-cytoplasmic trafficking of these patient-related SBDS proteins was disturbed. Further studies with a series of SBDS mutant proteins revealed that three distinct motifs determine the intracellular mobility of SBDS protein. A sumoylation motif in the C-terminal domain, that is lacking in patient SBDS proteins, was found to play a pivotal role in intracellular motility. Our structure-function analyses provide new insight into localization and motility of the SBDS protein, and show that patient-related mutant proteins are altered in their molecular properties, which may contribute to the clinical features observed in SDS patients.